Investigation of male reproductive traits of agronomic importance in cereals - Astrand, Johanna (2022)
Male fertility in flower development is important for breeding and yield stability in cereals. An intricate gene regulatory network in close association with environmental cues are required for formation of viable pollen and timely release of pollen from the anther. Hybrid breeding, the crossing of two elite cultivars, have the potential of generating varieties with increased yield and resistance to abiotic stresses but for crossing of elite parents for large scale seed production, certain qualities are required. The male parent should have high pollen production and effective dispersal whereas the female parent needs to exhibit male sterility to prevent self-pollination and be receptive of non-self pollen. In this project the impact of male traits on fertility and pollen dispersal have been studied in cereals to enhance understanding of processes useful for hybrid breeding. Three separate studies were carried out using forward and reverse genetic approaches to study traits related to male fertility and its effect on yield and traits of agronomic importance. In addition, anther development in angiosperm flowers was reviewed in an evolutionary perspective.